HUBUNGAN ANTARA KOMITMEN ORGANISASI DAN IKLIM ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PADA PT. COCA COLABOTTLING INDONESIA MEDAN - Jasman Saripuddin S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The purpose of this study was to know the relationship between the organizational commitment with employees satisfaction, and to find the relationship between the organizational commitment and organizational climate and amployees satisfaction that interconnected among one and the other at Coca cola Bottling Indonesian Medan Corporation.